Comparative study of fertilizer recommendations based on soil and leaf analysis vis a vis blanket recommendations of rubber board - Rajendran P V (Department of Plantation Crops and Spices, College of Horticulture, 1992)
A case study was made to assess the comparison of the dosage of fertilizer recommendation based on soil and leaf analysis vis-à-vis blanket recommendation of the rubber Board. Almost all estates in our country are practicing this method of fertilizer application and systematic data is available only from large estates.. Hence the case study was confined to Estate Sector. From the soil analytical values and economics of fertilizer usage of the nine estates studied, the following observations are made. 1. In general organic carbon status of the soil was found to be medium, though high values were also recorded in some fields. 2. The available phosphorus status of the soil was found to be low in most of the cases. 3. Except in one estate, all the estates were low in available potassium. The observation on the leaf analytical value are as follows: 1. Nitrogen status was in the medium range in most of the cases and only in few cases it is high. 2. Leaf phosphorus was found to be in medium to high range inspite of low available soil phosphorus. 3. Leaf potassium also followed same trend as leaf phosphorus. Economics of fertilizer usage based on soil and leaf analisis revealed the following: Savings in quantity as well as the cost of fertiliser could be made in seven estates. The cost of fertilizer saved per hectare was found to be Rs. 31.23. Eventhough in two estates no savings in quantity as well as in the cost of fertilizer could be made by adopting discriminatory approach, it was possible to maintain the balance among the nutrients in these estates preventing the likely drop of yield.